BMI1 enhancer polymorphism underlies chromosome 10p12.31 association with childhood acute lymphoblastic leukemia. Issue 11 (3rd October 2018) - de Smith, Adam J.; Walsh, Kyle M.; Francis, Stephen S.; Zhang, Chenan; Hansen, Helen M.; Smirnov, Ivan; Morimoto, Libby; Whitehead, Todd P.; Kang, Alice; Shao, Xiaorong; Barcellos, Lisa F.; McKean‐Cowdin, Roberta; et al.
Abstract : Genome‐wide association studies of childhood acute lymphoblastic leukemia (ALL) have identified regions of association at PIP4K2A and upstream of BMI1 at chromosome 10p12.31–12.2. The contribution of both loci to ALL risk and underlying functional variants remain to be elucidated. We carried out single nucleotide polymorphism (SNP) imputation across chromosome 10p12.31–12.2 in Latino and non‐Latino white ALL cases and controls from two independent California childhood leukemia studies, and additional Genetic Epidemiology Research on Aging study controls. Ethnicity‐stratified association analyses were performed using logistic regression, with meta‐analysis including 3, 133 cases (1, 949 Latino, 1, 184 non‐Latino white) and 12, 135 controls (8, 584 Latino, 3, 551 non‐Latino white). SNP associations were identified at both BMI1 and PIP4K2A . After adjusting for the lead PIP4K2A SNP, genome‐wide significant associations remained at BMI1, and vice‐versa ( p meta < 10 −10 ), supporting independent effects. Lead SNPs differed by ethnicity at both peaks. We sought functional variants in tight linkage disequilibrium with both the lead Latino SNP among Admixed Americans and lead non‐Latino white SNP among Europeans. This pinpointed rs11591377 ( p meta = 2.1 x 10 −10 ) upstream of BMI1, residing within a hematopoietic stem cell enhancer of BMI1, and which showed significant preferential binding of the risk allele to MYBL2 ( p = 1.73 x 10 −5 ) and p300 ( p = 1.55 x 10 −3 ) transcription factors using binomial tests on ChIP‐Seq data from a SNP heterozygote. At PIP4K2A, we identified rs4748812 ( p meta = 1.3 x 10 −15 ), which alters a RUNX1 binding motif and demonstrated chromosomal looping to the PIP4K2A promoter. Fine‐mapping chromosome 10p12 in a multi‐ethnic ALL GWAS confirmed independent associations and identified putative functional variants upstream of BMI1 and at PIP4K2A . Abstract : What's new? Several genomic loci have been associated with childhood acute lymphoblastic leukemia (ALL) but their mechanistic relevance remains unknown. Here the authors perform a first fine‐mapping analysis of a chromosome 10p12.31 region known to be associated with ALL. They confirm independent genome‐wide significant associations at nearby peaks upstream of the BMI1 polycomb ring finger oncogene and at phosphatidylinositol‐5‐phosphate 4‐kinase type 2 alpha (PIP4K2A). Using a multi‐ethnic linkage disequilibrium correlation approach, they define putative causal variants at both loci including in the enhancer region of BMI –a strategy, which could also be useful in causal variant discovery in other conditions.